The Eschatology of Malachi after Zechariah 14 - Goswell, Gregory (Journal of Biblical literature, 2013)
The recent scholarly appreciation of the Book of the Twelve as a unified canonical structure may influence the reading of Malachi with respect to its eschatology. More particularly, the prophecy of Malachi comes straight after Zechariah 14, and in that passage the end-time nations recognize God as king. In this article I argue that the eschatology of Zechariah 14 should affect our reading of the prophecy of Malachi. As in Zechariah 14, the international recognition of Yhwh’s rule is an important theme in Malachi’s picture of the future. Five key texts are considered (Mal 1:5, 11, 14; 3:4, 12), and each text is shown to be futuristic in orientation. The present cultic inadequacies exposed by the prophet are measured against an ideal past (3:4) and a glorious future (1:5, 11, 14; 3:4, 12). The proclamation of Malachi includes the eschatological hope of the renovation of the Jerusalemite cult and the universal worship of God among the nations.